The joint Africa-Europe partnership strategy: from Cairo to Lisbon: from an EU strategy for Africa to a joint Africa-EU strategy - Ferreira, Maria da Costa (2010)
Tese de mestrado, Políticas Europeias, Universidade de Lisboa, Faculdade de Letras, 2009